'Suits' and 'creatives': managerial control, the expropriation of fun and the manufacture of consent. (1st January 2007) - Bob Hughes
Abstract : Human skill poses a perennial problem to capitalist enterprises. This paper suggests that they have discovered, in the concept of 'creativity', a new weapon in the war on skill which simultaneously generates consent, sanctifies the use of inexperienced and expendable labour, and gives the manager even more power to control the worker while acting out the role of parent and protector. Creativity (as understood by modern managers) is an ineffable quality which 'we know when we see' — i.e. its existence and value are in the gift of the (managerial) beholder. Helpless and powerless, it is especially apt to be found amọngst the young and innocent. This paper draws on Michael Burawoy's study of 'Manufacturing Consent' in an engineering shop in the 1970s, and the author's own experience of working as a 'creative' in advertising agencies in the 1970s and 1980s.